FRET Visualization of Cyclic Stretch-Activated ERK via Calcium Channels Mechanosensation While Not Integrin β1 in Airway Smooth Muscle Cells - Fang, Xin; Ni, Kai; Guo, Jia; Li, Yaqin; Zhou, Ying; Sheng, Hui; Bu, Bing; Luo, Mingzhi; Ouyang, Mingxing; Deng, Linhong (Frontiers in Cell and Developmental Biology, 2022)
Mechanical stretch is one type of common physiological activities such during heart beating, lung breathing, blood flow through the vessels, and physical exercise. The mechanical stimulations regulate cellular functions and maintain body homeostasis. It still remains to further characterize the mechanical-biomechanical coupling mechanism. Here we applied FRET technology to visualize ERK activity under cyclic stretch stimulation in airway smooth muscle (ASM) cells, and studied the mechanosensing pathway. FRET measurements showed apparent ERK activation by mechanical stretch, which was abolished by ERK inhibitor PD98059 pretreatment. Inhibition of extracellular Ca2+ influx reduced ERK activation, and selective inhibition of inositol 1,4,5-trisphosphate receptor (IP3R) Ca2+ channel or SERCA Ca2+ pump on endoplasmic reticulum (ER) blocked the activation. Chemical inhibition of the L-type or store-operated Ca2+ channels on plasma membrane, or inhibition of integrin β1 with siRNA had little effect on ERK activation. Disruption of actin cytoskeleton but not microtubule one inhibited the stretch-induced ERK activation. Furthermore, the ER IP3R-dependent ERK activation was not dependent on Phospholipase C-IP3 signal, indicating possibly more mechanical mechanism for IP3R activation. It is concluded from our study that the mechanical stretch activated intracellular ERK signal in ASM cells through membrane Ca2+ channel mechanosensation but not integrin β1, which was mediated by actin cytoskeleton.